Science-Related Telecommunication - Norm Anderson (Journal of Research in Rural Education, 1993)
This particular summer workshop focused on a number of electronic projects for use in physics, chemistry, and biology. Most of the projects were prototypes and not all worked exactly as planned. Time did not permit refinement during the workshop, and many details were left to be worked on when we returned home. When the workshop ended, fortunately, the workshop directors had the foresight to provide for communication among participants via a telecommunication network through the University of Northern Iowa's mainframe computer. Now, in addition to the tremendous amount of work on our MBLprojects, we were spending ourlate afternoons and eveningslearning the basics of telecommunication. We were also faced with limited time on the computers for telecommunication, having to compete with regularly enrolled students on campus.